Cross-cultural validation of the Turkish Four-Dimensional Symptom Questionnaire (4DSQ) using differential item and test functioning (DIF and DTF) analysis - (:unkn) unknown (BMC, 2016)
Background: The Four-Dimensional Symptom Questionnaire (4DSQ) is originally a Dutch 50 item questionnaire developed in primary care to assess distress, depression, anxiety and somatization. We aimed to develop and validate a Turkish translation of the 4DSQ. Methods: The questionnaire was translated using forward and backward translation, and pilot testing. Turkish 4DSQ-data were collected in 352 consecutive adult primary care patients. For comparison, gender and age matched Dutch reference data were drawn from a larger existing dataset. We used differential item and test functioning (DIF and DTF) analysis to validate the Turkish translation to the original Dutch questionnaire. Through additional inquiry we tried to obtain more insight in the background of DIF in some items. Results: Twenty-one items displayed DIF but this impacted only the distress and depression scores. Inquiry among Turkish people revealed that the reason for DTF in the distress scale was probably related to unfavourable socio-economic circumstances. On the other hand, the likely explanation for DTF in the depression scale appeared to be grounded in culturally and religiously determined optimistic beliefs. Raising the distress cut-offs by 2 points and lowering the depression cut-offs by 1 point ensures that individual Turkish 4DSQ scores be correctly interpreted. Conclusions: The Turkish translation of the 4DSQ (named: Dort-Boyutlu Yakinma Listesi, 4BYL) measures the same constructs as the original Dutch questionnaire. Turkish anxiety and somatization scores can be interpreted in the same way as Dutch scores. However, when interpreting Turkish distress and depression scores, DTF should be taken into account.
Keywords: Distress; Depression; Anxiety; Somatization; Cross-cultural validation; Differential item functioning; Cultural beliefs; PRIMARY-CARE; DISORDER; ANXIETY; DEPRESSION; DISTRESS; VERSION; SCALE